2012
DOI: 10.5194/acp-12-857-2012
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric ice nuclei in the Eyjafjallajökull volcanic ash plume

Abstract: Abstract.We have sampled atmospheric ice nuclei (IN) and aerosol in Germany and in Israel during spring 2010. IN were analyzed by the static vapor diffusion chamber FRIDGE, as well as by electron microscopy. During the Eyjafjallajökull volcanic eruption of April 2010 we have measured the highest ice nucleus number concentrations (>600 l −1 ) in our record of 2 yr of daily IN measurements in central Germany. Even in Israel, located about 5000 km away from Iceland, IN were as high as otherwise only during desert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…Unlike field measurements, however, it has been suggested that all volcanic ash may have similar ice nucleation efficacy, initiating ice formation in a relatively narrow temperature range of approximately 250 to 260 K (Durant et al, 2008); however, these works are difficult to interpret quantitatively, especially in cases where the nucleation mode is unclear, frozen fractions are unavailable, or the available surface area has not been quantified. More recently, several studies have investigated the deposition-and/or immersion-mode ice nucleation properties of ash from the 2010 eruption of the Eyjafjallajökull volcano in Iceland (Steinke et al, 2011;Hoyle et al, 2011;Bingemer et al, 2012). The results of these studies, combined with previous studies on large, 250-300 µm ash particles from the 1980 Mt.…”
Section: G P Schill Et Al: Deposition and Immersion-mode Nucleatiomentioning
confidence: 70%
“…Unlike field measurements, however, it has been suggested that all volcanic ash may have similar ice nucleation efficacy, initiating ice formation in a relatively narrow temperature range of approximately 250 to 260 K (Durant et al, 2008); however, these works are difficult to interpret quantitatively, especially in cases where the nucleation mode is unclear, frozen fractions are unavailable, or the available surface area has not been quantified. More recently, several studies have investigated the deposition-and/or immersion-mode ice nucleation properties of ash from the 2010 eruption of the Eyjafjallajökull volcano in Iceland (Steinke et al, 2011;Hoyle et al, 2011;Bingemer et al, 2012). The results of these studies, combined with previous studies on large, 250-300 µm ash particles from the 1980 Mt.…”
Section: G P Schill Et Al: Deposition and Immersion-mode Nucleatiomentioning
confidence: 70%
“…Seifert et al 51 showed the existence of very efficient IN during the Eyjafjallajökull volcanic event. Bingemer et al 52 also observed a large increase of the IN concentration during this event, with IN surface densities of at least a factor two higher than that in other conditions (for example, air masses affected by mineral dust). Seifert et al 51 demonstrated the presence of ash-assisted formation of cirrus-like clouds in the troposphere over Leipzig and Maisach during several days after the first observational period (14-17 April 2010).…”
Section: Discussionmentioning
confidence: 95%
“…These results (Figure 3) indicated that ash particles might not act as efficient IN in deposition mode, but within the volcanic plume where ash concentrations greatly exceed background mineral dust concentrations their role in glaciating clouds would be important. We suggest that the reason volcanic ash particles investigated by previous studies [Schnell and Delany, 1976;Schnell et al, 1982;Hoyle et al, 2011;Steinke et al, 2011;Bingemer et al, 2012] were poor IN is because these ash particles may lack the necessary crystalline structural properties; however, further characterization of these ash particles is necessary to confirm the role of crystallinity toward ice nucleation.…”
Section: 1002/2015gl063270mentioning
confidence: 93%
“…On the other hand, Langer et al [1974] suggest that H 2 SO 4 produced from SO 2(g) oxidation associated with ash particles could reduce ice-forming efficiency, which lead to the conclusion that volcanic ash could be a poor source of atmospheric IN [Schnell and Delany, 1976;Schnell et al, 1982]. More recently, Bingemer et al [2012] found that ash particles collected near the eruption site were less efficient at À18°C and 119% relative humidity with respect to ice conditions in inducing ice nucleation compared to ambient particles collected in central Germany about 2200 km away from the eruption event. More specifically, Steinke et al [2011] observed that ice nucleation efficiency of ash particles is poorer than Arizona test dust (ATD; a commonly used proxy mineral for natural atmospheric mineral dust [e.g., Murray et al, 2012]) particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation